2023
DOI: 10.1038/s41419-023-05574-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces persistent adipose tissue damage in aged golden Syrian hamsters

Abstract: Coronavirus disease 2019 (COVID-19, caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2)) is primarily a respiratory illness. However, various extrapulmonary manifestations have been reported in patients with severe forms of COVID-19. Notably, SARS-CoV-2 was shown to directly trigger white adipose tissue (WAT) dysfunction, which in turn drives insulin resistance, dyslipidemia, and other adverse outcomes in patients with COVID-19. Although advanced age is the greatest risk factor for COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The inflammatory and antiviral response to SARS-CoV-2 infection is more prominent in visceral than subcutaneous fat ( 107 ) ( Fig. 1 ), and alterations in visceral adipose tissue are more persistent in old compared with young hamsters infected with the virus ( 176 ). Preclinical studies have shown that SARS-CoV-2 infection induces adipocyte dysfunction ( Fig.…”
Section: Effect Of Sars-cov-2 Infection On Tissue-specific Energy Met...mentioning
confidence: 99%
“…The inflammatory and antiviral response to SARS-CoV-2 infection is more prominent in visceral than subcutaneous fat ( 107 ) ( Fig. 1 ), and alterations in visceral adipose tissue are more persistent in old compared with young hamsters infected with the virus ( 176 ). Preclinical studies have shown that SARS-CoV-2 infection induces adipocyte dysfunction ( Fig.…”
Section: Effect Of Sars-cov-2 Infection On Tissue-specific Energy Met...mentioning
confidence: 99%
“…The consequences of a SARS-CoV-2 infection in aged hamsters have rarely been addressed 41 , 42 . Relative to young hamsters, aged animals had higher expression of genes encoding RNA-dependent RNA polymerase (RdRp) and envelope (E) protein and viral particles at 3 and 7 days post-infection (dpi) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have addressed the effect of advanced age on experimental SARS-CoV-2 infections in hamsters 41 , 42 , 57 60 . With the exception of Selvaraj et al 41 and Bogard et al 42 , these studies used middle-aged animals, aged from 5 to 8 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations